2006
DOI: 10.1215/s0012-7094-06-13332-x
|View full text |Cite
|
Sign up to set email alerts
|

The minimal lamination closure theorem

Abstract: We prove that the closure of a complete embedded minimal surface M in a Riemannian three-manifold N has the structure of a minimal lamination, when M has positive injectivity radius. When N is R 3 , we prove that such a surface M is properly embedded. Since a complete embedded minimal surface of finite topology in R 3 has positive injectivity radius, the previous theorem implies a recent theorem of Colding and Minicozzi: A complete embedded minimal surface of finite topology in R 3 is proper. More generally, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(105 citation statements)
references
References 14 publications
2
103
0
Order By: Relevance
“…Since the boundaries of the n leave every compact subset of * , for each compact set of * , the norms of the second fundamental forms of the n are uniformly bounded for values n sufficiently large and such a bound does not depend on the chosen compact set. Standard compactness arguments give that, after passing to a subsequence, n converges to a (weak) H -lamination L of * and the leaves of L are complete and have uniformly bounded norm of their second fundamental forms, see for instance [5].…”
Section: The Proof Of Theorem 11mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the boundaries of the n leave every compact subset of * , for each compact set of * , the norms of the second fundamental forms of the n are uniformly bounded for values n sufficiently large and such a bound does not depend on the chosen compact set. Standard compactness arguments give that, after passing to a subsequence, n converges to a (weak) H -lamination L of * and the leaves of L are complete and have uniformly bounded norm of their second fundamental forms, see for instance [5].…”
Section: The Proof Of Theorem 11mentioning
confidence: 99%
“…Abusing the notation, let J P H be the Jacobi function induced by taking the inner product of ∂ θ with the unit normal of P H , then J P H is positive. Finally, since the norm of the second fundamental form of P H is uniformly bounded, standard compactness arguments imply that its closure P H is an H -lamination L of , see for instance [5]. 1 , L 2 ⊂ that form the limit set of P H .…”
Section: Claim 44 There Exists At Least One Leaf L β In F That Intermentioning
confidence: 99%
See 1 more Smart Citation
“…After this, Meeks and Rosenberg proved that if Σ is a complete embedded minimal surface in R 3 which has positive injectivity radius, then Σ is proper, [17]. Finally, Meeks and Rosenberg proved that if f : Σ → R 3 is an injective minimal immersion, with Σ complete and of bounded curvature, then f is proper, [16].…”
Section: Introductionmentioning
confidence: 99%
“…An affirmative answer was given by Colding and Minicozzi in the embedded case, namely, they showed that embedded complete minimal surfaces must be unbounded [1]. More results in the embedded case were given in [7,8]. On the other hand, in the immersed case, a negative answer was given by Martin and Morales [5,6].…”
Section: Introductionmentioning
confidence: 99%